Harnessing of whey and CO2 for the production of Arthrospira (Spirulina) platensis microalgae biomass: a circular economy approach - Denis Cantú; Sharon Villegas-Rodríguez; Ruby Sheila Gines-Palestino; Jair Reyes; jorge Cruz-Mérida; Daniel Montalvo Salinas (Acta Scientiarum. Biological Sciences, 2024)
The production of microalgae biomass has a high cost due to the composition of the culture medium; therefore, the cultivation of Arthrospira (Spirulina) platensis using carbon dioxide (CO2) and whey could be considered an effective method of obtaining microalgae biomass while reducing greenhouse gas emissions and a sustainable solution for the treatment of dairy industry wastewater. As a result, the microalgae biomass produced has the potential to become a valuable source of energy (biodiesel), food (for humans or animals), and other compounds such as vitamins and pigments. According to circular economy and development practices, this paper aimed to investigate the growth of Arthrospira platensis biomass using CO2 and whey as a substitute for culture medium. The effects of different whey dilution and culture conditions on biomass productivity, nutrients, and chemical oxygen demand (COD) removal were examined in batch experiments. The results show that the highest biomass production (3.31 g·L-1) was achieved in 19-day experiments using a modified Schlösser culture medium with 500 mL CO2 as a carbon source. In the cultures with whey, removal of organic load percentages of 89.16%, 98.88%, and 97.76% was reached on the tenth day in the cultures with 1, 5, and 9 g COD·L-1, respectively. The highest lipid content of 7.07 g lipids 100 g-1 biomass was reached using 500 mL of CO2 as a carbon source, demonstrating that subjecting the culture to a nutrient deficit causes an accumulation of lipids as long as there is light and CO2 available.